Articulation and expressive interpretation in Wang Jianzhong’s transcription ‘A Hundred Birds Pay Homage to The Phoenix’ - Zhang, Xiao Pei; Loo, Fung Chiat; Ang, Mei Foong; Yeoh, Pei Sze (Artseduca, 2024)
Background: According to Western classical music literature, the primary criteria for interpretation in performance practice is strict adherence to the original score and musical notation. When a composer or arranger transcribes a work to a different instrument, it becomes more complex because the interpretation of a work involves fidelity to the composer’s intention. This indefinitely increases uncertainty, particularly when the transcription lacks clear indications that allow a more liberal interpretation. Aim: Thus, this article examines the use of articulation and how it affects the expressivity in Wang Jianzhong’s piano transcription, ‘A Hundred Birds Pay Homage to the Phoenix’. The analysis discusses the interpretation of articulation in this transcription. Methodology: This study adopts a musicological analysis by a case study and literature review from related research that focuses on a synthesis of musical elements to achieve a conceptual interpretation from a performance and theoretical perspective. Result and Conclusion: The analysis demonstrates that the original timbre and musical emotion can be successfully conveyed on the piano through the use of different articulation strategies, despite the composer’s lack of extensive notations.